The average rate of change of <em>f(x)</em> on -3 ≤ <em>x</em> ≤ 3 is given to be
(<em>f</em> (3) - <em>f</em> (-3)) / (3 - (-3)) = -2.5
If <em>f</em> (-3) = 14, then
(<em>f</em> (3) - 14) / (3 + 3) = -2.5
(<em>f</em> (3) - 14) / 6 = -2.5
<em>f</em> (3) - 14 = -15
<em>f</em> (3) = -1
Answer:
10/13
Step-by-step explanation:
-7-(3)
----------
-4-(9)
Answer:
31
Step-by-step explanation:
50 x 0.62 = 31
Answer:
Answer:
85t
Step-by-step explanation:
1. Volume of a cone: 1. V = (1/3)πr2h 2. Slant height of a cone: 1. s = √(r2 + h2) 3. Lateral surface area of a cone: 1. L = πrs = πr√(r2 + h2) 4. Base surface area of a cone (a circle): 1. B = πr2 5. Total surface area of a cone: 1. A = L + B = πrs + πr2 = πr(s + r) = πr(r + √(r2 + h2))
hope this helps